Informational nudges as an effective approach in raising awareness among young adults about the risk of future disability. Issue 1 (1st July 2016) - Miesler, Linda; Scherrer, Corinne; Seiler, Roger; Bearth, Angela
Abstract: As many consumers have neither sufficient time nor the cognitive and motivational resources to deal with complex insurance decisions, the mere provision of information might not be enough to influence consumer perception and choice. The way such information is presented might also affect any decision made. This paper focuses on the risk of becoming unable to continue in a profession as a result of illness or an accident. In collaboration with an insurance company, we examined the effectiveness of 'informational nudging' (i.e. providing information which acts as a nudge) in sensitizing young adults to the potential risk of disability. In a pre‐study, an online survey ( n  = 1003) was conducted to assess the main barriers preventing young Swiss adults from participating in private provision. Based on the results of the pre‐study, we developed four 'informational nudges' and tested their effects on risk awareness and insurance choices among young adults using an online experiment ( n  = 240). We found that by presenting information on a company website in such a way that heuristics such as availability or loss aversion were exploited, enhanced risk awareness and a corresponding increase in insurance preferences were observed to some degree. However, the informational nudges did not motivate the participants to investigate the issues any further. Indeed, the results suggested that informational nudging could be an effective tool in raising participant awareness, but that future research is needed to understand better the interplay between automatic and deliberate processes activated by the informational nudges. Copyright © 2016 John Wiley & Sons, Ltd.